FLÁVIO SUPLICY DE LACERDA: RELAÇÕES DE PODER NO CAMPO ACADÊMICO/POLÍTICO PARANAENSE E O PROCESSO DE FEDERALIZAÇÃO E MODERNIZAÇÃO DA UNIVERSIDADE DO PARANÁ (1930-1971) - Souza, Eliezer Felix de (2016)
This thesis aims to analyze Flávio Suplicy de Lacerda‘s trajectory. We sought to understand the power relations in the academic and political fields in the state of Paraná that conditioned his rise and his permanence as chancellor for about two decades. The justification of this analysis is linked to the place he occupied in the academic, political and intellectual scenario in Paraná and Brazil‘s history, as a professor, secretary, minister, and, above all, chancellor of the Federal University of Paraná (UFPR) between the years 1949 and 1971. The various positions held by him permit to problematize Flávio Suplicy‘s initiatives in the academic and political field, in an attempt to understand the strategies that contributed to his entry into the field of power and enabled him to actively participate in the federalization process and expansion of the University of Paraná as well as reach the post of Minister of Education during Castello Branco‘s government. The hypothesis is that, when he established relationships between the professional field of engineering, academic and political field in Paraná, he gained prominance that gave him conditions to assume management positions. The theoretical framework, constituded by the discussions of Intellectual History and Pierre Bourdieu‘s theoretical and methodological propositions, and sources (minutes, annuals, reports, newspapers - Gazeta do Povo, O Dia e Diário da Tarde), allow us to understand the social space in which Suplicy de Lacerda was inscribed and explain the process that resulted in the transformation of the capital invested in strategies to enter the academic field and expand his potential of action in that space and in the political field. Specifically, this thesis is organized into four chapters, in which we discuss the dimensions about family investment, integration into the academic and liberal professional environment, as well as integration in the social space with personalities such as Plinio Tourinho, Brasil Pinheiro Machado and Ney Braga, who had direct participation in the path that rose Suplicy de Lacerda to the power field of university (chancellor) and political sphere (State Secretary / Minister of Education). The theoretical and empirical mobilization, undertaken during this research, enables us to state that Flávio Suplicy joined political leaderships of the State of Paraná and Brazil and professors of the Federal University of Paraná, gaining recognition of the group to keep himself as a chancellor for several years. Consequently, the academic field gained visibility among the military, being appointed as the first Minister of Education during the Civicmilitary Dictatorship. In summary, as administrator (Chancellor/Minister), he adopted an authoritarian modernization model that resulted in an intense expansion construction of the Federal University of Paraná and permanent disciplinary surveillance presented in the academic field. He attributed an important role to the university as it was up to it the task to rise Paraná and Brazil to the ‗new‘, the ‗modern‘, which consisted of strong investment in the expansion of the university services, but under the direction of a controled authoritarian politics of social movements, particularly of the students, whose ultimate expression was the Law 4.464/1964 (Suplicy Law) that put the National Union of Students in illegality, without, however, stop suffering strong student resistance.